2021
DOI: 10.1161/circulationaha.120.049098
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free DNA to Detect Heart Allograft Acute Rejection

Abstract: Background: After heart transplantation, Endomyocardial biopsy (EMBx) is used to monitor for acute rejection (AR). Unfortunately, EMBx is invasive and its conventional histologic interpretation has limitations. This is a validation study to assesses the performance of a sensitive blood biomarker— percent donor-derived cell-free DNA (%ddcfDNA) — for detection of AR in cardiac transplant recipients. Methods: This multicenter, prospective cohort study recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
218
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(228 citation statements)
references
References 33 publications
9
218
1
Order By: Relevance
“…23 Figure 3 show the correlation of dd-cfDNA elevation with biopsy grades of ACR and AMR, as well as echocardiographic findings. 24 Another such commercially available assay is Prospera (Natera, San Carlos, CA, USA). Utilizing technology that was initially created to detect fetal cfDNA in prenatal testing, this test utilizes NSP-based PCR to measure dd-cfDNA for the detection of rejection.…”
Section: Gene Expression Profiling (Gep)mentioning
confidence: 99%
See 2 more Smart Citations
“…23 Figure 3 show the correlation of dd-cfDNA elevation with biopsy grades of ACR and AMR, as well as echocardiographic findings. 24 Another such commercially available assay is Prospera (Natera, San Carlos, CA, USA). Utilizing technology that was initially created to detect fetal cfDNA in prenatal testing, this test utilizes NSP-based PCR to measure dd-cfDNA for the detection of rejection.…”
Section: Gene Expression Profiling (Gep)mentioning
confidence: 99%
“…Agbor-Enoh et al found that, for similar histopathologic grades, the percent dd-cfDNA was higher in AMR as compared with ACR, rose preceding the histologic diagnosis, and had a distinct fragment length with shorter fragments of cfDNA. 24 These unique insights can help facilitate more accurate diagnosis of AMR.…”
Section: Cell-free Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Elevations in dd-cfDNA are also present in the setting of allograft injury in heart transplant recipients [32][33][34]. An early retrospective analysis of 7 heart transplant recipients performed by Snyder et al in 2011 demonstrated increases in dd-cfDNA in the setting of acute rejection with an AUC of 0.84 at a threshold of 1.7% for the detection of ≥ Grade 2R/3A ACR or AMR [35].…”
Section: Dd-cfdna In Heart Transplant Recipientsmentioning
confidence: 99%
“…Ordering a genomic test is commonplace in oncology and becoming the standard of care for conditions from developmental disabilities to heart transplant rejection. 1,2 Over 26 million people in the USA have purchased a genomic test online with a growing proportion interested in their risk of common diseases like cancer, dementia, and heart disease. Given this exponential growth, it is time to expand the vision of genomic quality of care beyond the accuracy of genetic tests to include the clinical processes that determine how these tests are used.…”
mentioning
confidence: 99%